An Analysis of Preservice Elementary Teacher Ability in Creative Writing Containing Character Education with Local Wisdom Persepective - Retno Winarni; St Y Slamet; Jenny IS Poerwanti; Muhammad Ismail Sriyanto; Septi Yulisetiani; Ahmad Syawaludin (Jurnal Ilmiah Sekolah Dasar, 2021)
Poetry can be an integrative media for character education in learning in elementary schools. However, the important role of poetry has not been matched by the results of writing poetry in elementary schools. This study aims to analyze the ability of preservice elementary teacher ability in poetry writing containing character education with local wisdom persepective. Mix method research approach is used with research design is triangulation design. The research subjects were 35 students of the elementary school teacher education program. The data were obtained through the technique of writing poetry tests and interviews. The analysis of the test used aspects of poetry writing skills. The research findings provide views that students have been able to write poetry with their own imagination, include the meaning of poetry, the advice, and are able to integrate character values with local wisdom. Mastery of the diction aspect is the lowest among other aspects that need to be improved. Recommendations of this research to educators and future research as a review for developing effective Indonesian language learning in the elementary school teacher education program, especially in productive language skills, namely creative writing with character education and local wisdom.